Social Revolution and Authoritarian Durability. (3rd October 2020) - Lachapelle, Jean; Levitsky, Steven; Way, Lucan A.; Casey, Adam E.
ABSTRACT: This article explores the causes of authoritarian durability. Why do some authoritarian regimes survive for decades, often despite severe crises, while others collapse quickly, even absent significant challenges? Based on an analysis of all authoritarian regimes between 1900 and 2015, the authors argue that regimes founded in violent social revolution are especially durable. Revolutionary regimes, such as those in Russia, China, Cuba, and Vietnam, endured for more than half a century in the face of strong external pressure, poor economic performance, and large-scale policy failures. The authors develop and test a theory that accounts for such durability using a novel data set of revolutionary regimes since 1900. The authors contend that autocracies that emerge out of violent social revolution tend to confront extraordinary military threats, which lead to the development of cohesive ruling parties and powerful and loyal security apparatuses, as well as to the destruction of alternative power centers. These characteristics account for revolutionary regimes' unusual longevity.